QUALITY CONTROL OF MULTI-SLICE CT-SCAN AIRCRAFT USING PHANTOM CHART MODEL 610 AT MAKASSAR HAJI HOSPITAL - Fira, Nurul Magfirawati; Dewang, Syamsir; Astuty, Sri Dewi; Muliadin, Muliadin (Universitas Mataram, 2022)
This study aims to determine and analyze the quality control phantom chart of a CT-scan plane from the CT number's accuracy, the CT number's uniformity, and the uniformity of noise against the phantom. The AAPM CT Performance Phantom with the model 610 offers a single object to measure several different CT performance parameters. The Phantom design is based on the guidelines presented in the AAPM. From the measurement results, the accuracy of the CT number is still following the tolerance standard; namely, the value of passing the test Â± 4 for the accuracy of the CT number, and the value of passing the test 2 is the uniformity of the CT number. Based on the Standard Regulations of the Head of the Nuclear Energy Supervisory Agency, stating that the value of accuracy and uniformity of the CT number from the CT scan image obtained in research conducted on a multi-slice CT scan plane at the Radiology Installation of the Makassar Haji Regional General Hospital shows the value of passing the test or still within PERKA BAPETEN standard.